Strategic Resource Relationship Model, Adaptability to Environmental Dynamics, Implementation of School-Based Management and Vocational School Competitiveness - Jamil, Amidatus Sholihat; Kamdi, Waras; Hadi, Syamsul; Patmanthara, Syaad (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
The aim of this research is to obtain the best relationship model between strategic resources, adaptability to environmental dynamics, and the implementation of school-based management on competitiveness in vocational schools which is thought to have an indirect relationship through existing mediating variables, without ignoring the direct relationship of each variable. This research is included in explanatory research with the statistical analysis technique used, namely Structural Equation Modeling (SEM). The population and sample in this study were 397 public and private vocational school teachers in East Java Province. Research data was collected through the distribution of questionnaires conducted online and offline. The results of hypothesis testing show that: (1) strategic resources have a positive and significant effect on environmental dynamics; (2) strategic resources have a positive and significant effect on the implementation of SBM; (3) adaptability to environmental dynamics has a positive and significant effect on SBM implementation; (4) strategic resources have a positive and significant effect on competitiveness; (5) SBM implementation has a positive and significant effect on competitiveness; (6) environmental dynamics have a positive and significant effect on competitiveness through the implementation of SBM; (7) strategic resources have a positive and significant effect on competitiveness through environmental dynamics and SBM implementation; (8) strategic resources have a positive and significant effect on competitiveness through the implementation of MBS; and (9) strategic resources have a positive and significant effect on the implementation of SBM through environmental dynamics.